Unveiling the disc structure in ultraluminous X-ray source NGC 55 ULX-1. Issue 3 (2nd September 2022) - Barra, F; Pinto, C; Walton, D J; Kosec, P; D'Aì, A; Di Salvo, T; Del Santo, M; Earnshaw, H; Fabian, A C; Fuerst, F; Marino, A; Pintore, F; et al.
ABSTRACT: Ultraluminous X-ray sources (ULXs) are the most extreme among X-ray binaries in which the compact object, a neutron star or a black hole, accretes matter from the companion star, and exceeds a luminosity of 10^39 erg s^-1 in the X-ray energy band alone. Despite two decades of studies, it is still not clear whether ULX spectral transitions are due to stochastic variability in the wind or variations in the accretion rate or in the source geometry. The compact object is also unknown for most ULXs. In order to place constraints on to such scenarios and on the structure of the accretion disc, we studied the temporal evolution of the spectral components of the variable source NGC 55 ULX-1. Using recent and archival data obtained with the XMM- Newton satellite, we modelled the spectra with two blackbody components which we interpret as thermal emission from the inner accretion flow and the regions around or beyond the spherization radius. The luminosity–temperature (L–T) relation of each spectral component agrees with the L ∝ T 4 relationship expected from a thin disc model, which suggests that the accretion rate is close to the Eddington limit. However, there are some small deviations at the highest luminosities, possibly due to an expansion of the disc and a contribution from the wind at higher accretion rates. Assuming that such deviations are due to the crossing of the Eddington or supercritical accretion rate, we estimate a compact object mass of 6–14 M⊙, favouring a stellar-mass black hole as the accretor.